"I couldn't say goodbye": Thematic analysis of interviews with bereaved relatives who lost their loved ones during the COVID-19 pandemic - Vlckova, Karolina; Polakova, Kristyna; Houska, Adam; Zindulkova, Marketa; Loucka, Martin (BMC palliative care, 2024)
BACKGROUND: Delivering serious news is usually challenging for healthcare professionals and the pandemic of COVID-19 and related restrictions brought additional challenges in this process. AIMS: To explore the experience of bereaved relatives with receiving serious news from healthcare professionals during the pandemic COVID-19. DESIGN: A qualitative study using thematic analysis and a codebook approach of data collected in semi-structured interviews with bereaved relatives. SETTING/PARTICIPANTS: Data were collected from July to August 2022 in person/via phone with bereaved relatives who lost their relatives during the pandemic (from March 2020 to March 2022). Participants were recruited using a convenience sample and snowball method through social media and through one university hospital palliative care unit that invited bereaved relatives of deceased patients treated at the unit to participate in this study. RESULTS: A total of 22 participants, consisting of 4 men and 18 women, were interviewed for this study. Most of the participants were sons or daughters of individuals who had died (5 grandchildren, 14 sons/daughters, 2 spouses, 1 great-niece). Six themes were identified: Burden caused by visit ban, Fear of COVID-19, Inappropriate behaviour and communication of healthcare professionals, High need for emotional support, Need for detailed and honest communication, Tendency to make excuses for mistakes and lapses by healthcare professionals. CONCLUSIONS: Delivering serious news during a pandemic was negatively influenced by a lack of contact with patients and a lack of support and empathetic communication with staff. Overcoming these circumstances can be achieved by frequent communication using various communication tools (such as videoconferences or phone calls), and maintaining empathy and honesty in the communication process.
Keywords: Male; Family; rodina; rozhovory jako téma; Middle Aged; Interviews as Topic; Qualitative study; COVID-19 pandemic; Delivering bad news; Adult; Aged; dospělí; mužské pohlaví; senioři; sociální opora; Social Support; pandemie; komunikace; SARS-CoV-2; Bereavement; kvalitativní výzkum; ztráta blízké osoby; lidé; ženské pohlaví; Humans; Health communication; End of life; Communication; Pandemics; Qualitative Research; Female; lidé středního věku; COVID-19